Analysis of holistic integrated curriculum on contemporary models of higher education institutions in Malaysia - Rahimah, Embong; Nadhirah, Nordin; Abdul Hakim, Abdullah; Fadzli, Adam; Nor Afizan, Che Omar; Rosnani, Hashim (2016)
This paper aim to analyze the concept and theoretical framework of Holistic Integrated Curriculum, and what would they demand from Higher Education Institutions in the case of Malaysia. In the context of Muslim society. its malaise and backwardness is rooted from educational dualism, co-existence of modern secular and traditional religious sciences. As a practical solution, integration of both sciences into a holistic integrated curriculum is suggested to solve this problem. Hence, the Islamic heritage of higher education should be explored by comparing it with the contemporary models of so-called integration made possible, as in the case of International Islamic University Malaysia and Islamic Science University Malaysia. This paper proposed a renewed concept of 'Holistic Integrated Curriculum' (H IC) and its theoretical framework which would be helpful to avoid superficial and artificial integration of the curriculum, rather showing a way for accommodation of different models.